TOTAL QUALITY MANAGEMENT MODEL FOR EMPLOYEE PERFORMANCE (STUDY AT PT. TRISULA ULUNG MEGASURYA KEPAHIANG-BENGKULU) - Reflis Reflis; Melli Suryanty; Musriyadi Nabiu; Nusril Nusril; Windi Septika (Jurnal Agrisep)
This study aims for 1)  determine the effect of Total Quality Management (TQM) on employee performance, and 2) examine the TQM model of employee performance at  PT.  TUM, Kepahiang-Bengkulu. This study uses Structural Equation Model Analysis (SEM) with the Partial Least Square (PLS) method. PLS is a variant-based SEM statistical method simultaneously by carrying out measurement model tests and structural model testing with data scales and sample sizes that do not need to be large. The data used were obtained by interviewed the 86 employees of PT. Trisula Ulung Megasurya in Kepahiang Regency. The research found that the variable X2 (strategic planning) and X3 (analysis and information) have a significant effect on latent variable employee performance, while the variables X1 (leadership), X4 (human resource management(HRM)), and X5 (management process) do not. Based on the analysis of the SEM/PLS model which is formed in measuring the effect of TQM on employee performance, the model is Y = 3,652 X2 + 2,311 X3.